The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.2135/cropsci2013.09.0623
|View full text |Cite
|
Sign up to set email alerts
|

Time and Temperature Interactions in Freezing Tolerance of Winter Wheat

Abstract: 1523 RESEARCH C old acclimation, or cold-hardening, occurs in many plant species in response to a period of low, above-freezing temperatures and short daylengths, as occur in the autumn in temperate regions of the world. Cold acclimation is associated with a plethora of metabolic changes that are thought to contribute to the ability to withstand subsequent freezing to potentially damaging tempera-). Specifically with wheat (Triticum aestivum L.), Herman et al. (2006) found that plants that had been cold-acclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Both populations experience temperatures that trigger cold acclimation. The range of conditions over which cold acclimation is induced is poorly known and is likely to vary across taxa, but 4°C has been shown to induce cold acclimation in Arabidopsis thaliana (Alonso‐Blanco et al., ; Hannah et al., ; Zhen and Ungerer, ) and winter wheat (Zhu et al., ; Skinner, ). In winter at the SW site, soil temperatures are usually below freezing for more than 80 days, and temperatures can reach as low as −11°C, with air temperatures even colder (Oakley et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Both populations experience temperatures that trigger cold acclimation. The range of conditions over which cold acclimation is induced is poorly known and is likely to vary across taxa, but 4°C has been shown to induce cold acclimation in Arabidopsis thaliana (Alonso‐Blanco et al., ; Hannah et al., ; Zhen and Ungerer, ) and winter wheat (Zhu et al., ; Skinner, ). In winter at the SW site, soil temperatures are usually below freezing for more than 80 days, and temperatures can reach as low as −11°C, with air temperatures even colder (Oakley et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…While some degree of cold hardening happens at temperatures as high as 10–12°C, for wheat and for other cold‐hardy perennial grasses (e.g., Gay and Eagles, 1991), complete acclimation does not occur until temperatures are well below this induction threshold and typically well below 5°C (Fowler, 2008; Ganeshan et al, 2009). In fact, further cold adaptation requires temperatures well below freezing (Herman et al, 2006; Veisz et al, 1996); individual freezing events even after acclimation have been achieved are associated with further short‐term transcriptional responses (Skinner, 2009); and maximal cold adaptation may require temperatures as low as −10°C (Skinner, 2014; Skinner and Bellinger, 2017). Photoperiod also has a role in achieving or prolonging cold tolerance in some wheat cultivars (Mahfoozi et al, 2001) but not in others (Limin and Fowler, 2006), and in general appears to be much less important than temperature in inducing cold tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the hard freeze, we decreased the temperatures to −2 ˚C and added ice chips to the plants to facilitate ice nucleation (Case et al, 2014). The plants were subjected to a period of freezing of −8 ˚C for 24 h. During the freezing period, plants were kept in the dark following other studies to avoid potential confounding effects of temperature and Circadian rhythm (Case et al, 2014;Skinner, 2014;Skinner & Bellinger, 2017). To simulate a freeze-thaw cycle, we then raised the chamber temperature to 4 ˚C for 2 d with 50 PAR with a 4-h photoperiod.…”
Section: Freezing Tolerance Assaymentioning
confidence: 99%
“…We then repeated the process of ramping down the temperature and ice chipping and then subjected the plants to another period at −8 ˚C, this time for 48 h. These exposure times and temperatures in this experiment were chosen from among preliminary trials (results not shown) as those that produced the largest relative differences in freezing tolerance between the control line Norstar and select southern accessions. While other studies have assayed freezing tolerance in winter wheat at colder temperatures, typically for shorter durations (Case et al, 2014;Skinner, 2014;Skinner & Bellinger, 2017;Skinner & Garland-Campbell, 2008), here we investigate the effect of slightly warmer temperatures sustained over a longer duration.…”
Section: Freezing Tolerance Assaymentioning
confidence: 99%
See 1 more Smart Citation